USING THE PROJECT METHOD IN ORGANIZING EXTRACURRICULAR ACTIVITIES OF STUDENTS OF PROFESSIONAL EDUCATIONAL INSTITUTIONS (Scientific journal of the Fergana State University, 2023)
The article considers the possibilities of organizing the method of projects in professional educational institutions for the meaningful organization of extracurricular activities and the development of knowledge, skills and abilities of students in the subjects studied. The stages of extracurricular organization of the students' project method and the tasks of the subjects of the educational process are outlined. The possibilities of the formation of general cultural, general professional and professional competencies of future specialists as a result of the effective organization of extracurricular activities are revealed. The article describes the formation of the integrity of the system of universal knowledge, skills and abilities of students, as well as the possession of skills of independent work with various sources of information and experience of independent work in the process of project activities.